EFFICACY OF ULTRASOUND GUIDED PERIPHERAL NERVE BLOCKS IN TRIGEMINAL NEURALGIA PATIENTS RECEIVING COMBINATION DRUG THERAPY - Dr. Narendra Singh Yadav; Dr. Avinash Kumar; Dr. Veerendra Singh Yadav; Dr. Jitendra Singh Yadav (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Neuralgia involves pain along a damaged nerve, often resulting from injury or underlying pathology. Maxillofacial pain—originating from structures such as meninges, cornea, pulp, mucosa, and TMJ—comprises various neurological disorders that significantly impact patients' quality of life. Trigeminal neuralgia (TN), characterized by sudden, severe, shock-like facial pain, is among the most intense and common facial pain disorders. Diagnosis is primarily clinical, with neurovascular compression as a key etiology. Current treatments include pharmacotherapy, nerve blocks, and surgical procedures, but limitations such as adverse effects and procedural risks necessitate alternative approaches. Ultrasound-guided nerve blocks, combined with multi-drug regimens, present a minimally invasive option with potential benefits. Objective:  To evaluate the efficacy of ultrasound-guided peripheral nerve blocks combined with pharmacological therapy in patients with TN, focusing on pain reduction measured by the Numeric Rating Scale (NRS), safety, and patient satisfaction. Methods:  This prospective observational study included 33 patients with clinically diagnosed TN. All received a standardized three-drug regimen (carbamazepine, amitriptyline, baclofen) for 15 days, followed by ultrasound-guided nerve blocks targeting trigeminal divisions. Pain intensity was assessed at baseline, 15, and 30 days. Data analysis involved comparison of NRS scores and satisfaction levels. Results:  Significant reductions in NRS scores were observed in both groups, with a greater decrease in the nerve block group (from 7.75 to 1.25) versus the drug-only group (from 6.24 to 1.76) at 30 days (p